Paracentrotus lividus - Madeira, Patrícia; Kroh, Andreas; Cordeiro, Ricardo; De, António M.; Martins, Frias; Ávila, Sérgio P. (Zenodo, 2019)
Paracentrotus lividus (Lamarck, 1816) (Fig. 25) Reports for the Azores: Echinus lividus Lamarck, 1816 — $ Drouët 1861: 210; Barrois 1888: 31; Toxopneustes lividus (Lamarck, 1816) — $ Agassiz 1863: 23; $ Simroth 1888: 231; Strongylocentrotus lividus (Lamarck, 1816) — $ Agassiz 1872: 446–447, pl. 5b, fig. 3, pl. 24, fig. 25; $ Barrois 1888: 75; John 1889: 285; $ Koehler 1895a: 225, 1898: 24; Jackson 1912: 162; Paracentrotus lividus (Lamarck, 1816) — Koehler 1914b: 278; Mortensen 1927a: 306–309, figs. 175–177; $ Cadenat 1838: 367; Nobre 1938: 118–119, figs. 48–49, 66; $ Mortensen 1943a: 157–168, figs. 69–72, pl. 17, figs. 2–3, pl. 22, figs. 1–9, pl. 57, figs. 1–3, 11, 12, 20; $ Chapman 1955: 399; Harvey 1956: 51, 65; $ Tortonese 1965: 337–341, figs. 160–162; $ Marques 1983: 5–6, 1984: 105; Moyse & Tyler 1995: 678–680, fig. 12.8; Pereira 1997: 334; Pérez-Ruzafa et al. 1999: 52–53, 2002: 285–286; $ Cardigos et al. 2005: 165; García-Diez et al. 2005: 50; Schultz 2006: 194–195, figs. 361–363; Haddad & Barreiros 2008: 9, fig. 3a; Ávila et al. 2009: 27, 2010: 56; Micael & Costa 2010: 323; $ Micael et al. 2010: 329; $ Wisshak et al. 2010: 2382; Madeira et al. 2011: 249–250, figs. 5C, 6C, 7C; Micael et al. 2012: 3, 5. non Psammechinus microtuberculatus (Blainville, 1825) — $ Marques 1983: 5 [misidentification]. See: Mortensen (1943a); Schultz (2006). Occurrence: Mediterranean Sea and northeast Atlantic, from Ireland (Mortensen 1927a), along the coast of Europe (Nobre 1938) to Mauritania (Chapman 1955), including the archipelagos of the Azores (Marques 1989), Madeira (Alves et al . 2001), Selvagens (Pérez-Ruzafa et al. 2002), Canaries (Pérez-Ruzafa et al. 2003) and Cape Verde (Pérez-Ruzafa et al. 1999). Depth: 0–80 m (Tortonese 1965), rarely below 30 m (Picton 1993); AZO: 0–40(?207) m (Koehler 1898, herein). Habitat: preferentially rocky shores where it can bore holes in the rock (Schultz 2006); diet mainly of algae (Mortensen 1943a). Larval stage: planktotrophic (Emlet 1995). Fossil fauna: remains of this ...